Fluorescent Gold Nanoclusters for In Vivo Shortwave-Infrared Imaging. (27th September 2021) - Tsuboi, Setsuko; Jin, Takashi
Abstract : Gold nanoclusters (Au-NCs) are unique fluorescent nanomaterials that can be used for in vitro and in vivo bioimaging. Au-NCs are less toxic, and their size is much smaller than that of other fluorescent nanomaterials such as quantum dots. The emission wavelengths of Au-NCs depend on the nanocluster size, which can be controlled by the reaction conditions. Recently, shortwave-infrared (SWIR) emitting Au-NCs have attracted much attention for bioimaging. SWIR fluorescence (900–1400 nm) enables deep tissue imaging due to the weak absorption and scattering of the SWIR fluorescence by tissues. Since the autofluorescence of tissues is almost zero in the SWIR region, SWIR fluorescence imaging results in high contrast images compared to visible and near-infrared imaging. For the SWIR fluorescence imaging, the development of biocompatible SWIR fluorescent probes is crucial. Although several types of SWIR fluorescent probes based on quantum dots, rare-earth-doped nanoparticles, and organic dyes have been appeared, there are very few examples of SWIR probe which cytotoxicity is low enough to use in biomedical fields. Herein, we present the synthesis, and optical properties of bovine serum albumin (BSA) capped Au-NCs (Au-NCs@BSA), which emit at the SWIR region. We demonstrate the efficacy of Au-NCs@BSA for in vivo SWIR fluorescence imaging of brain vasculatures, blood vessels, lymph nodes and tumors in mice.